Shale Lithofacies and Its Effect on Reservoir Formation in Lower Permian Alkaline Lacustrine Fengcheng Formation, Junggar Basin, NW China - Tang, Yong; He, Wenjun; Zheng, Menglin; Chang, Qiusheng; Jin, Zhijun; Li, Jiao; Zhang, Yuanyuan (Frontiers in Earth Science, 2022)
Lower Permian Fengcheng Formation is considered to be a high-quality alkaline lacustrine shale oil resource in the Junggar Basin, NW China. Based on core and thin section observation, X-ray diffraction, scanning electron microscope, low-pressure N2 adsorption, and high-pressure mercury intrusion porosimetry, different shale lithofacies, and pore structures were examined. According to the mineral composition, shales in well My 1 are divided into five types: dolomitic mudstone, calcareous mudstone, siliceous mudstone, tuffaceous mudstone, and argillaceous mudstone, each of which shows its pore structure distribution. Intragranular pores, inter-crystalline pores associated with clays and pyrites, dissolution pores, and microfractures were commonly observed. There are three segments of pore structures including <50 nm, 50 nm-4 μm, and >4 μm. Clay minerals mainly contribute to mesopores, especially in argillaceous mudstones. The dissolution of carbonate minerals and feldspars is significant for macropores predominantly in dolomitic mudstones and tuffaceous mudstones, respectively. Micron-scale microfractures associated with laminae dominate in dolomitic mudstones. Therefore, the dolomitic mudstones, especially with lamination, and tuffaceous mudstones are proposed to be favored shale lithofacies with great exploration potential in the Mahu Sag.